Magnitude, distribution and determinants of non-utilization of antenatal care services among women in low- and middle-income countries: Insights for implementation of WHO recommendations - Tadesse Tarik Tamir; Deresse Abebe Gebrehana; Alebachew Ferede Zegeye; Bewuketu Terefe; Berhan Tekeba (PLoS ONE, 2025)
Introduction Pregnancy is a pivotal stage that fosters health and prepares women and their families for the transition to parenthood. Antenatal care (ANC) encompasses the services provided by skilled healthcare professionals to pregnant women and adolescent girls, ensuring optimal health outcomes for both mother and child throughout pregnancy. The majority of maternal and child deaths occur in low- and middle-income countries (LMICs), where access to essential healthcare services, including ANC, remains a significant challenge. This study was aimed to assess the magnitude, spatial distribution, and determinants of non-utilization of ANC services in LMICs. Methods This study analyzed data from the most recent Demographic and Health Surveys conducted between 2015 and 2024, encompassing a total of 47 LMICs. The analysis included a weighted sample of 480,068 women. We employed spatial analysis to illustrate the geographic distribution of non-utilization of antenatal care and hierarchical analysis to identify contributing factors. ArcGIS 10.8 and Stata 17 were utilized for spatial and hierarchical analysis, respectively. Adjusted odds ratios with 95% confidence intervals (CIs) were calculated, and factors were considered statistically significant at a p-value of less than 0.05. Results Pooled magnitude of non-utilization of ANC among women in LMICs was at 10.59%, ranging from 40.05% in Afghanistan to 0.76% in Burundi, with many regions in several countries identified as hotspots for ANC non-utilization. Factors significantly associated with higher odds of non-utilization included having no (AOR = 3.28; 95% CI: 3.02–3.55) or low (primary schooling: AOR = 1.81; 95% CI: 1.67–1.96, and secondary schooling: AOR = 1.28; 95% CI: 1.18–1.38) education, being unmarried (AOR = 1.35; 95% CI: 1.29–1.41), lower wealth index (poorest: AOR = 1.87; 95% CI: 1.77–1.98), poorer: AOR = 1.45; 95% CI: 1.38–1.54, middle: AOR = 1.17; 95% CI: 1.11–1.24, and richer: AOR = 1.09; 95% CI: 1.04–1.15), having no media exposure (AOR = 1.68; 95% CI: 1.64–1.73), residing in rural areas (AOR = 1.05; 95% CI: 1.02–1.09), facing distance issues to health facilities (AOR = 1.31; 95% CI: 1.28–1.34), and the low-income level of the countries (AOR = 2.27; 95% CI: 1.23–6.74). Conclusion A significant proportion of women in LMICs have not utilized antenatal care services. Factors at the individual, community, and country levels contribute to this non-utilization. Policymakers should focus on addressing these barriers to achieve the WHO recommendation of eight or more ANC contacts in LMICs.